Time-Varying Properties of Respiratory Fluctuations in Pupil Diameter of Human Eyes - Yoshida, H.; Yana, K.; Okuyama, F.; Tokoro, Takashi (Methods of Information in Medicine, 1994)
The time varying properties have been investigated of respiratory components in fluctuations of the pupil diameter (PDF) of the human eye. PDF and instantaneous lung volume were simultaneously measured for 45 minutes under natural binocular viewing conditions. The short-term Fourier transform and the autoregressive signal modeling together with the recursive least squares algorithm have been applied for the estimation of nonstationary power spectra. Data analysis showed a bursting type non-sta-tionarity in the appearance of the respiratory component in PDF.
Keywords: Pupil Diameter; Instantaneous Lung Volume; Autonomic Nervous Activity; Adaptive Signal Processing; Spectral Analysis